Makna Simbolik Upacara Wulla Poddu dalam Masyarakat Loli Sumba Barat Nusa Tenggara Timur - Flora Ceunfin (EKSPRESI, 2010)
The Symbolic Meaning of the Wulla Paddu Ceremony. The research on the Wulla Paddu ceremony of the Loli community in West Sumba, East Nusa Tenggara province, intends to find out the symbolic meaning expressed in local traditional music called talla. The ceremony represents ritual activity during the Holy month of Loli New Year observed once a year according to the cultural calendar of the local community who believed in the supreme being of Marapu. The aim of the ceremony is to show respect and to express gratitude and requests to Ama wolu-Ama rawi (The Creator) through the intercession of Marapu. Wulla Paddu ceremonial event is organized in several phases which are always accompanied by talla music. The performance of talla music represents a symbolic meaning in terms of worshipping the supreme being of Marapu. The performance of talla music has been compulsory as an important part of the annually observed Wulla Paddu where the rhythm of the music reflects the symbolic meaning of the ceremony. The outcome of this research has shown that the performance of talla music in Wulla Paddu ceremony has played an important role in revealing the meanings of religious, social, and cultural symbols. The music is worthy to be preserved in accordance with its local cultural values, as well as an intangible heritage of West Sumba people, that hopefully will remain observed by the Loli community for many generations to come.  Keywords: Talla, Marapu, Loli community